Update on Sunflower Diseases in Argentina - Colombo, Denis Nahuel; Fass, Monica Irinia; Erreguerena, Ignacio Antonio; Filippi, Carla Valeria; Martinez, Maria Carolina; Dominguez, Matías; Martínez, Ana Laura; Aguilera, Pablo; Deperi, Sofía Irene; Heinz, Nicolas; Ben Guerrero, Emiliano; Carrera, Alicia; et al. (De Gruyter, 2025)
The moderate genetic diversity of cultivated sunflower, along with a changing environment, make sunflowers subject to the attack of many pests and diseases, with great economic impact. In Argentina, fungi and oomycetes produce four of the most challenging diseases: Sunflower Verticillium Wilt, Phomopsis Stem Canker, Sclerotinia Head Rot and Sunflower Downy Mildew. Efficient crop management to reduce the impact of pathogens requires resistant hybrids, recommendations for agricultural practices, and epidemiological monitoring to aid decision-making. However, each pathosystem has its own caveats. The integration of genotypic and phenotypic knowledge of sunflower breeding resources with the characterization of pathogens is critical to effectively assisting breeders in improving plant resistance and reducing yield losses. Below, we provide an overview of the latest scientific knowledge on each pathosystem and the strategies being pursued for breeding disease-resistant hybrids.